The effect of task characteristics on enterprise resource planning system success with user characteristics and organizational characteristics as mediating variables - Grace Theresia Pontoh; Deng Siraja; Muhammad Achyar Ibrahim (Journal of Economics, Business, and Accountancy Ventura, 2019)
Enterprise Resource Planning(ERP) is an integrated system that provides a wide range of benefits for the company, but there are still many companies who have unsuccessfully implemented ERP system. This study aimed to analyze the effect of the task characteristic and the success of Enterprise Resource Planning (ERP) on the success of ERP, with the user characteristic and organizational characteristic as mediating variables. The data were collected by using a questionnaire distributed directly to users of Enterprise Resource Planning (ERP) in Indonesian companies listed in Indonesia Stock Exchange (ISE). The data were processed by using Partial Least Square (PLS). It was found that the suitability of the task significantly affects the success of an ERP system, either directly or mediated by the user variable characteristic and organizational characteristic. Task difficulty also significantly affects the success of an ERP system if mediated by the convenience variable (user characteristic). The success of the ERP system is determined by based tasks and task complexity through the system the user's convenience in using the information system.